2018
DOI: 10.29024/aogh.2364
|View full text |Cite
|
Sign up to set email alerts
|

Cost Effectiveness of Mobile Health for Antenatal Care and Facility Births in Nigeria

Abstract: Background:The use of mobile technology in the health sector, often referred to as mHealth, is an innovation that is being used in countries to improve health outcomes and increase and improve both the demand and supply of health care services. This study assesses the actual cost-effectiveness of initiating and implementing the use of the mHealth as a supply side job aid for antenatal care. The study also estimates the cost-effectiveness ratio if mHealth was also used to encourage and track women through facil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“… 45 - 48 The role of digital health in extending access to healthcare services was emphasised in 4 of the 5 studies. 45 - 48 4 studies reported on mobile health implementations; 1 was an initiative supporting AIDS care 49 and the other 3 varying aspects of Reproductive, Maternal, Neonatal and Child health (RMNCH). 45 , 47 , 48 The fifth study dealt with costing a hypothetical teleradiology initative.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 45 - 48 The role of digital health in extending access to healthcare services was emphasised in 4 of the 5 studies. 45 - 48 4 studies reported on mobile health implementations; 1 was an initiative supporting AIDS care 49 and the other 3 varying aspects of Reproductive, Maternal, Neonatal and Child health (RMNCH). 45 , 47 , 48 The fifth study dealt with costing a hypothetical teleradiology initative.…”
Section: Resultsmentioning
confidence: 99%
“… 45 - 48 4 studies reported on mobile health implementations; 1 was an initiative supporting AIDS care 49 and the other 3 varying aspects of Reproductive, Maternal, Neonatal and Child health (RMNCH). 45 , 47 , 48 The fifth study dealt with costing a hypothetical teleradiology initative. 46 While all but 1 study achieved the JBI criterion of a description of alternatives (JBI2), including comparison between an intervention and a comparator, 46 only 1 study met the more stringent criterion of analysis of intervention alternatives (FCM-DH3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a previous study has suggested that home-based therapy can be as effective as office-based therapy if a biofeedback system is applied [ 70 ]. In addition to increasing training accuracy, the home-based mHealth training app may enable the participants to attend various training programs (eg, the 8-week program adopted in this study) without the burden of visiting clinics as frequently or the need to pay extra costs [ 71 , 72 ]. Thus, the time- and cost-effectiveness of mHealth programs with tongue-strengthening exercises may represent strong points for promoting their widespread use.…”
Section: Discussionmentioning
confidence: 99%
“…The cost and benefit analysis of online ANC service is also required to assess the feasibility of continuing online ANC service by the decision-making authorities ( 31 ). Of relevance, analysis of mobile health's cost-effectiveness for ANC and facility births showed that mobile health programs were relatively inexpensive and saved lives (for the dollar investment) in Nigeria ( 32 ).…”
Section: Introductionmentioning
confidence: 99%